Argamassa geopolimérica à base de lodo de estação de tratamento de água calcinado - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
In the process of water treatment for public supply, which is made in the water treatment plants (WTPs), a waste conventionally called sludge is formed. As in the soil, the main components of WTP sludge are silicon (Si), aluminum (Al) and iron (Fe). This composition allowed to suggest that this waste could be used in the production of inorganic polymers - the geopolymers. While conventional polymers are formed by carbon structures, geopolymers are composed of Si and Al structures. They are obtained by dissolving aluminosilicates materials in highly alkaline solution. Among the possible applications, they can be used as pastes, mortars and concretes, in replacement of Portland cement, which is the most used binder in civil construction worldwide. To verify the suitability of the sludge as a geopolymer precursor, this waste was properly benefited by means of mechanical grinding and calcination at 750 °C for 6 hours, being characterized before and after its processing. The results of chemical and mineralogical analyzes proved the adequacy of calcined WTP sludge as a geopolymeric raw material. To check the influence of the sources of raw water abstraction intake on the WTP sludge characteristics and consequently in the properties of materials produced from sludge-based, samples of this waste were collected under the influence of two different water sources. With these samples it produced of two geopolymeric mortars. The final products were properly characterized and the results proved that regardless of the peculiarities of water sources, WTP sludge can be used as a geopolymeric raw material. In the thermal tests the two mortars produced showed indications of refractory bahavior and have been free of calcium hydroxide, therefore, it can be inferred that they are free matrices of deleterious actions of this compound. In the mechanical tests, at 28 days of cure, they reached mechanical strengths of 57 and 79 MPa, on average. Some results evidenced the need for improvements in the formulation of mortars, but in general, it was verified that the use of WTP sludge as a geopolymer precursor material is a very promising alternative for the destination of this waste, making it valuable and useful product for society.
Keywords: lodo de ETA; Geopolímero; Argamassa geopolimérica; Geopolymer; Geopolymeric mortar; ENGENHARIAS: ENGENHARIA CIVIL